Cardiac regeneration - Ieda, Masaki; Zimmermann, Wolfram-Hubertus (Cardiac and vascular biology., 2017)
This Volume of the series Cardiac and Vascular Biology offers a comprehensive and exciting, state-of-the-art work on the current options and potentials of cardiac regeneration and repair. Several techniques and approaches have been developed for heart failure repair: direct injection of cells, programming of scar tissue into functional myocardium, and tissue-engineered heart muscle support. The book introduces the rationale for these different approaches in cell-based heart regeneration and discusses the most important considerations for clinical translation. Expert authors discuss when, why, and how heart muscle can be salvaged. The book represents a valuable resource for stem cell researchers, cardiologists, bioengineers, and biomedical scientists studying cardiac function and regeneration.